(untitled) (ENTHYMEMA, 2023)
This essay aims to investigate how narration has exploited its adaptive capacity within the convergent culture in relation to television seriality. In particular, it now seems that cultural products are profoundly transmedia. In this light narratives in this era have become more rapid and multifaceted so that each text has a certain number of paratexts. Narration of contemporaneity works on the expansion of storytelling through different media, which extend the original franchise in different ways. This essay takes into account through a series of paratexts the fact that the transmedia and cross-media extensions of a franchise become a new form of narrative typical of the contemporary world, which adds understanding to the original product.